Diagnosis Penyakit Kelamin Laki-Laki Menggunakan Metode Bayesian Network - Yori Tri Cuswantoro; Nurul Hidayat; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Venereal disease is a disease that attacks the male and female genital organs that are usually transmitted through sex or oral sex. In Indonesia, the most common sexually transmitted diseases are syphilis and gonorrhea, the prevalence of sexually transmitted diseases in Indonesia is very high, in Jakarta the prevalence of gonorrhea is 29.8%, syphilis 25.2% and chlamydia 22.7%. Everyone can get a sexually transmitted disease. The tendency of increasing the spread of this disease is caused by the sexual behavior of multiple partners, and the existence of a high premarital sexual relationship. Bayesian Network is a simple Probabilistic Graphical Model (PGM) built from probabilistic theory and graph theory. The variables needed in this study are symptoms of male genital disease. After the symptoms are entered, it will be processed by the Bayesian Network. The result of the bayesian network is the diagnosis of male genital disease. The accuracy obtained from the test results is 88.57%.